Pengaruh Ketepatan Waktu Publikasi Laporan Keuangan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Sri Bulkia; Husnurrofiq Husnurrofiq; Hairul Hairul; M. Haris Syafitri (International Forum of Researchers and Lecturers, 2024)
Public companies that have shares on the Indonesia Stock Exchange (IDX) must submit their annual financial reports in a timely manner. This annual report contains significant information about the company's progress and performance for one year. Therefore, delays in submitting the report can have a negative impact, especially on investor confidence and internal parties of the company (IDX). The timeliness of publication of financial reports, namely profitability, leverage, and liquidity, in property and real estate sector companies listed on the Indonesia Stock Exchange between 2020 and 2022. This study has a quantitative approach. The study population includes all property and real estate companies listed on the Indonesia Stock Exchange. The research sample was selected using the purposive sampling method, namely by selecting samples that meet certain criteria, and the total number of samples taken was 13 companies from the 2020-2022 period. The results of this study indicate that the variable test of the profitability, leverage, and liquidity ratios in property and real estate sector companies listed on the Indonesia Stock Exchange in 2020-2022 shows that these factors do not have a significant effect on the timeliness of publication of financial reports.